The PDMA handbook of innovation and new product development - Bstieler, Ludwig; Noble, Charles H. (John Wiley & Sons, Inc., 2023)
"Thank you for purchasing this book. We are delighted and honored to bring you the 4th edition of the PDMA Handbook of Innovation and New Product Development. Our partners at the Product Development and Management Association (PDMA) and Wiley & Sons Publishing are as enthusiastic as we are to see this almost completely new edition of a very popular and useful book come to life. The goal of this Handbook, as in prior editions, is to provide an introduction, a thought-provoking series of essays, and a practical guide for managers and thought leaders working in new product development (NPD) and innovation. Astute readers of our prior editions may notice that the title has slightly changed in this 4th edition. We now appropriately highlight innovation as a key focus of what we are to explore in addition to our continuing emphasis on new product development. Our deepest thanks go to the wonderful collection of authors who have contributed to this book and to prior editions. In this collection, they share their thoughtful insights and broad experiences to bring you a compilation that represents the state-of-the-art in the field. One of the unique features of this book series has always been that our authors represent a balance of outstanding practitioners, world-class consultants and leading-edge academic researchers. Thus, you will find here both applied, first-hand insights from the field, and findings from academics who have been studying innovation and new product development using the latest techniques. Combined, we share with you knowledge that is powerful, practical, and thought-provoking. This book is a collection of 32 chapters representing a host of different voices. The style of the chapters presented here also varies greatly. Some chapters are extremely hands-on and step-by-step, providing practical tools to apply in your organization. Other chapters may present new concepts, ideas, and approaches that are meant to stimulate your thinking and to help you find creative ways to study or apply these thoughts in your workplace or in your research"--